2020
DOI: 10.2147/cmar.s281605
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Ultrasound-Guided Minimally Invasive Biopsy in the Diagnosis or Treatment of Breast Nodules

Abstract: Purpose To explore the clinical value of ultrasound-guided minimally invasive biopsy of breast nodules for diagnosis and treatment of patients with no positive clinical signs on manual breast examination. Methods We performed a retrospective review of 136 patients with no signs on breast palpation who underwent ultrasound-guided minimally invasive biopsy. A total of 63 patients underwent breast nodule resection from October 2018 to December 2019 at the General Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ultrasound is the primary method used to differentiate between benign and malignant breast nodules 27 . Our result indicated that patient’s age, birth number, shape, resistance index, calcification, axillary lymph node, internal echo, margin, alder grade and background echotexture were significantly correlated with benign and malignant breast nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is the primary method used to differentiate between benign and malignant breast nodules 27 . Our result indicated that patient’s age, birth number, shape, resistance index, calcification, axillary lymph node, internal echo, margin, alder grade and background echotexture were significantly correlated with benign and malignant breast nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, breast ultrasonography should be the primary adjunctive test for axillary masses in Asian populations or in patients with small breast glands. However, no matter what kind of imaging examination method is used, a satisfactory diagnostic coincidence rate cannot be achieved (17)(18)(19)(20). Thus, because of their rare occurrence and involvement of unusual sites, they pose a significant challenge for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The literature on UMIBS has mainly reported its efficacy and prognosis but has rarely reported the teaching method. 4,5 The rapid development of UMIBS and the lag of the efficiency teaching mode put forward higher requirements for medical educators.…”
Section: Introductionmentioning
confidence: 99%